2010
DOI: 10.1016/j.foreco.2010.07.054
|View full text |Cite
|
Sign up to set email alerts
|

Responses of forest trees to single and multiple environmental stresses from seedlings to mature plants: Past stress history, stress interactions, tolerance and acclimation

Abstract: a b s t r a c tForest trees are exposed to a myriad of single and combined stresses with varying strength and duration throughout their lifetime, and many of the simultaneous and successive stress factors strongly interact. While much progress has been achieved in understanding the effects of single stresses on tree performance, multiple interacting stress effects cannot be adequately assessed from combination of single factor analyses. In particular, global change brings about novel combinations of severity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
494
1
14

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 636 publications
(524 citation statements)
references
References 314 publications
(393 reference statements)
15
494
1
14
Order By: Relevance
“…Although there was no direct effect of herbaceous biomass on oak survival or growth (ESM 1), increased herbaceous cover in elevated CO 2 plots may have reduced abiotic stress for the germinating oak acorns under the denser herbaceous canopy. This pattern also emerged early on in oak development when oaks were smaller and likely more vulnerable to abiotic stressors, such as heat and drought (Niinemets 2010).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Although there was no direct effect of herbaceous biomass on oak survival or growth (ESM 1), increased herbaceous cover in elevated CO 2 plots may have reduced abiotic stress for the germinating oak acorns under the denser herbaceous canopy. This pattern also emerged early on in oak development when oaks were smaller and likely more vulnerable to abiotic stressors, such as heat and drought (Niinemets 2010).…”
Section: Discussionmentioning
confidence: 82%
“…Tukey tests for multiple comparisons between different levels of CO 2 and time were not possible using the GLMM with a multinomial distribution in the SAS program; for this reason letters indicating significance between groups are not displayed some type of environmental severity (e.g., extreme temperatures, increased surface soil drying, and increased rates of evapotranspiration). Aboveground cover may be particularly important for smaller/younger seedlings, which tend to have less well-developed root systems and less nonstructural C reserves to survive short periods of stress (Niinemets 2010). As plants grow in size, their root systems become more developed, and they become less susceptible to short periods of extreme abiotic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to drought may also make trees more vulnerable to insects (Gaylord et al, 2013) and pathogens (Niinemets, 2010). Drought stress enhanced the development of Diplodia pinea on Italian cypress (Madar et al, 1995), Fusarium compactum on Cupressus sempervirens (Madar et al, 1996) and Sphaeropsis sapinea on Pinus resinosa (Blodgett et al, 1997a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthesis and growth rates decline with increasing tree age and size, while support biomass in roots, stem and branches accumulates and the concentrations of nonstructural carbohydrates increase. It was suggested that combined stresses can infl uence survival of large trees even more than chronic exposure to a single predictable stress such as drought [36].…”
Section: Discussionmentioning
confidence: 99%